Pathological anatomy of the placenta in pregnant women with pyelonephritis. - Gubina-Vakulik, G. I.; Gancheva, E. V.; Naumova, O. V. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. In different countries 5-15% of pregnancies occur on the background either gestational or chronic pyelonephritis. Knowledge about the pathological and compensatory changes in placental tissue due to pyelonephritis in pregnant women are incomplete. Objective. To analyze the results of a comprehensive morphological study of the placenta in pregnant women with pyelonephritis at term and late preterm pregnancy taking into account the data of the presence and activity of a specific enzyme of renal parenchyma (transamidinase) with the aim to differentiate pathological and compensatory changes in the placenta. Methods. 79 placentas with chronic and gestational pyelonephritis, 15 placentas of comparison group were investigated. In addition to description of the morphological changes in placenta tissue micromorphometry and immunohistochemical reaction for 8 clotting factors (mark of endothelial cells and villi syncytiotrophoblast) were performed. Results. Damage of the placental tissue of infectious-toxic and hypoxic etiology (small-focal or diffuse macrophage-lymphocyte infiltration of the basal lamina, presence of intervillous fibrinoid, sclerosis of stroma, foci of calcification, thrombosis in the vessels of the placenta and on the surface of the villi) accompanied the formation of compensatory mechanisms, including hypertrophy and hyperplasia of structures at different levels: total hypertrophy of the placenta, hyperplasia of terminal villi, hyperplasia of syncytiotrophoblast nuclei, hyperplasia of capillaries, thin syncytial-capillaries membrane in terminal villi, increase in the number of syncytial-capillaries membranes, hyperplasia and hypertrophy of syncytial nodules. Conclusion. It has been established that in transamidinase-positive cases compensatory mechanisms do not compensate progressive damage of the placental tissue. Increasing production of 8th clotting factor in the terminal villous syncytiotrophoblast can be considered as adaptive mechanism due to the increased destruction of the villous epithelium at pyelonephritis in pregnant women, to create preconditions for the rapid formation of parietal thrombus, reducing the isolation of the maternal and fetal blood flow.